2010
DOI: 10.1021/la103591f
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Acid−Base Interaction Energy at Solid Interfaces

Abstract: We have studied acid-base interactions at solid-liquid and solid-solid interfaces using interface-sensitive sum frequency generation (SFG) spectroscopy. The shift of the sapphire hydroxyl peak in contact with several polar and nonpolar liquids and polymers was used to determine the interaction energy. The trend in the interaction energies cannot be explained by measuring only water contact angles. Molecular rearrangements at the sapphire interface, to maximize the interaction of the acid-base groups, play a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(107 citation statements)
references
References 18 publications
4
103
0
Order By: Relevance
“…The amount of red-shift is related to the interaction strength according to the Badger–Bauer equation; the higher the shift, the stronger the interaction strength. The calculated interaction strength between pristine aggregate glue and sapphire O-H groups (Supplementary Table 1 ) is comparable to the strongest interaction between carbonyl groups and sapphire surface O–H groups reported in literature 29 , 42 . We also observe C–H stretching vibrations in the 2800–3050 cm −1 region.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The amount of red-shift is related to the interaction strength according to the Badger–Bauer equation; the higher the shift, the stronger the interaction strength. The calculated interaction strength between pristine aggregate glue and sapphire O-H groups (Supplementary Table 1 ) is comparable to the strongest interaction between carbonyl groups and sapphire surface O–H groups reported in literature 29 , 42 . We also observe C–H stretching vibrations in the 2800–3050 cm −1 region.…”
Section: Resultssupporting
confidence: 83%
“…When sapphire O–H groups are in contact with air (air/sapphire interface), a sharp peak at ~3720 cm −1 is observed for the sapphire hydroxyl groups. However, when sapphire O–H groups come in contact with other molecules such as poly(methyl methacrylate) or polystyrene, the O–H peak becomes broader and shifts to lower wavenumbers due to acid–base interactions between the sapphire O–H groups and the other molecules in contact 29 , 42 . The amount of red-shift is related to the interaction strength according to the Badger–Bauer equation; the higher the shift, the stronger the interaction strength.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in SSP polarization, the 3645 cm −1 peak not only decreased in intensity but also shifted to lower wavenumber. It is possible that the weaker acid−base interactions were The correlation between the shift of OH peak and the strength of interactions can be quantified using the Badger− Bauer equation −ΔH = mΔν + C. 30,47 If we assume that the hydrogen-bonding and van der Waals interactions between hexadecanol molecules in the self-assembled monolayer were the same as those in the solid bulk, the increased monolayer melting temperature should be a result of the acid−base interactions between alcohol molecules and sapphire surface OH groups. To calculate the strength of the acid−base interactions, which were disrupted during the monolayer melting transition, we have subtracted the portion of the acid−base interactions that existed at 120°C from those at 65°C…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Since SFG can also monitor the position and shift of the surface hydroxyl peak, this technique can also be used to directly determine the strength of the hydrogen-bonding interaction and its influence on stabilizing the ordered monolayer above the bulk T m . 30,31 In addition to the structure of hexadecanol SAM in contact with its own melt, it is also intriguing to understand how the SAM influences the crystal structure upon freezing (referred to as s−s interface). It has been shown that long chain alcohols exhibit three polymorphic phases: the α rotator phase, β crystalline phase, and γ crystalline phase ( Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, the shift in the surface sapphire O–H peak can be used to calculate the strength of the acid–base interactions (hydrogen bonding is a subset of acid–base interactions). 57 For example, in the previously reported study, the ester groups in poly(methyl methacrylate) showed stronger interaction (O–H peak is shifted to 3580 cm –1 compared to free O–H peak at 3720 cm –1 ) than functional groups in polystyrene (3645 cm –1 ) when in contact with a sapphire substrate. 58 Similarly, since the interfacial adhesion of the deprotected elastomer is higher, we speculated that there might be a larger shift for the deprotected elastomer as compared to protected elastomer, which would indicate a stronger bond between the hydroxyl groups of catechol and the sapphire.…”
Section: Results and Discussionmentioning
confidence: 81%